ANALISIS TINGKAT KETERAMPILAN SOSIAL DALAM PELAKSANAAN KEGIATAN KKN PADA MAHASISWA PRODI PPKN UNIVERSITAS RIAU TAHUN 2018-2020 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by development Of the field In science and technology that requires an individual to be able to master it, the results of these effects affect social values and social skills that tend to disappear from society. In other words, it will be more relevent, if social skills have a positive impact on society without being influenced by science and technology. As social beings, the nature of society wants to always develop or change, whether that happens sooner or later affects various aspects, especially the education aspect. This research method is descriptive quantitative, the data collection instrument used by questionnaire consisting of 27 statements. The population in this study were students of the University of Riau. Sampling in this study using Incidental Sampling Technique.Based on the recapitulation in the discussion of students on the implementation of KKN activities, the amount obtained is (39.1%) obtained from the sum of Very Often (SS) + Often (S) which is 6.1% + 33% = 39.1% which lies in the range 25.01%-50%. This shows that the implementation of the Real Work Lecture (KKN) can be categorized as